Synthesis of N-Acyl Carbamates and Oxazolidinones Using HClO4-SiO2 as Catalyst Under Solvent-Free Conditions - Juan Yang, Li; Yang, Yuping; Dong, Ruoyi (Asian Journal of Chemistry, 2010)
Silica supported perchloric acid catalyzes efficiently the reaction of carbamates and oxazolidinones with anhydrides in the presence of silica sulfuric acid under solvent-free conditions. All the reactions were done at room temperature and the N-acyl carbamates and oxazolidinones were obtained with high yields and purity via an easy work-up procedure. This method is attractive and is in a close agreement with green chemistry.